The Use of Game-Based Learning Method to Improve Seven-Grader Students' English Learning Motivation and Achievement at MTs Negeri 2 Malang - Istifadah; Ahmadi (ELITE JOURNAL, 2023)
ABSTRACT This study aims to increase students' motivation and learning outcomes in English courses. The research subject is 32 seven grader students at MTs Negeri 2 Malang. This research was carried out in two cycles consisting of 4 stages: planning, implementation, observation and reflection. Learning motivation data were taken through field observations and interviews, which were then analyzed descriptively. The learning outcomes data were taken from the Pre-Test and Post-Test before and after the class action. The Pre-Test and Post-Test scores were then analyzed quantitatively by calculating the percentage of complete learning outcomes and the class average obtained. The results showed a significant increase in learning motivation and learning outcomes in the two cycles. The percentage of learning outcomes indicates this: the Pre-Test score completeness in the first cycle was 40.62% and increased in the Post-Test to 71.87%. In the second cycle, the completeness score on the Pre-Test was 15.62%, which increased significantly in the Post-Test at 75%. Keywords: Learning Motivation; Learning Outcomes; Game-Based Learning; Learning Method.